Functional conservation of an AP2/ERF transcription factor in cuticle formation suggests an important role in the terrestrialization of early land plants. (16th September 2022) - Kim, Ryeo Jin; Lee, Seat Buyl; Pandey, Garima; Suh, Mi Chung
Abstract: The formation of a hydrophobic cuticle layer on aerial plant parts was a critical innovation for protection from the terrestrial environment during the evolution of land plants. However, little is known about the molecular mechanisms underlying cuticle biogenesis in early terrestrial plants. Here, we report an APETALA2/Ethylene Response Factor (AP2/ERF) transcriptional activator, PpWIN1, involved in cutin and cuticular wax biosynthesis in Physcomitrium patens and Arabidopsis. The transcript levels of PpWIN1 were 2.5–fold higher in gametophores than in the protonema, and increased by approximately 3– to 4.7–fold in the protonema and gametophores under salt and osmotic stresses. PpWIN1 harbouring transcriptional activation activity is localized in the nucleus of tobacco leaf epidermal cells. Δppwin1 knockout mutants displayed a permeable cuticle, increased water loss, and cutin- and wax-deficient phenotypes. In contrast, increased total cutin and wax loads, and decreased water loss rates were observed in PpWIN1 -overexpressing Arabidopsis plants. The transcript levels of genes involved in cutin or wax biosynthesis were significantly up-regulated in PpWIN1 -overexpressing Arabidopsis lines, indicating that PpWIN1 acts as a transcriptional activator in cuticle biosynthesis. This study suggests that Arabidopsis WIN1/SHN1 orthologs may be functionally conserved from early to vascular land plants. Abstract : The occurrence of AP2/ERF transcription factor PpWIN1, which is functionally conserved in cuticle formation of Physcomitrium patens and Arabidopsis, may be important for the terrestrialization of early land plants.